Femtoscopy of the J/ψ-nucleon interaction - Krein, Gastão [UNESP] (EDP Sciences, 2022)
I discuss the prospects of using femtoscopy in high-energy proton-proton and heavy-ion collisions to learn about the low-energy J/ψ-nucleon interaction. Femtoscopy is a technique that makes it possible to obtain spatiotemporal information on particle production sources at the femtometer scale through measurements of two-hadron momentum correlation functions. These correlation functions also provide information on low-energy hadron-hadron forces as final-state effects. In particular, such correlation functions give access to the forward scattering amplitude. One can express the forward amplitude as the product of the J/ψ chromopolarizability and the nucleon’s average chromoelectric gluon distribution, the latter being relevant to the problem of the origin of the nucleon mass. I will present the results of a recent study using the information on the J/ψ-nucleon interaction from lattice QCD simulations to compute J/ψ-nucleon correlation functions. The calculated correlation functions show clear sensitivity to the final-state interaction. I conclude discussing open issues regarding the use of the effective range expansion formula to fit experimental data for small scattering lengths and large effective range parameters.